Oncocytoma of Oral Cavity Mimicking as Jaw Tumor - Aloke Bose Majumdar; Shib Shankar Paul; Gautam Sarker; Souradeep Ray (Case Reports in Otolaryngology)
Oncocytoma of major salivary gland is a fairly common benign tumour encountered, but its occurrence in oral minor salivary gland is a rare entity. Here we report a case of a giant minor salivary gland oncocytoma mimicking a jaw tumour which was successfully excised along with a review of literature.